2009
DOI: 10.1111/igc.0b013e31819c9fa0
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Adjuvant Chemotherapy for Node-Positive Cervical Adenocarcinoma

Abstract: We examined the effectiveness of postoperative adjuvant chemotherapy for node-positive cervical adenocarcinoma. During the period from 1994 to 2002, 98 consecutive patients with clinical stage I and II cervical adenocarcinoma were treated surgically without having undergone any prior treatment. Surgical procedures included radical hysterectomy, bilateral salpingo-oophorectomy, and pelvic lymphadenectomy. Postoperatively, 21 patients were found to have lymph node metastasis, and all were treated with chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Other therapeutic strategies must be determined for those who need postoperative treatment or other primary treatment options. Takeshima et al [21] reported a study of more than 20 node-positive patients with cervical adenocarcinoma who were treated postoperatively with chemotherapy. The survival data showed that the effectiveness of postoperative chemotherapy was equal to or better than that of RT in node-positive patients with cervical adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Other therapeutic strategies must be determined for those who need postoperative treatment or other primary treatment options. Takeshima et al [21] reported a study of more than 20 node-positive patients with cervical adenocarcinoma who were treated postoperatively with chemotherapy. The survival data showed that the effectiveness of postoperative chemotherapy was equal to or better than that of RT in node-positive patients with cervical adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, the probability of mortality in early-stage disease recurrent endometrial cancer being a common factor among patients with mortality. This study also identified higher age and advanced stages as contributing factors [11]. Another report by Lortet-Tieulent and colleagues, examining endometrial cancer prevalence in the United States and Europe, discussed higher mortality rates among older patients and those with comorbidities such as diabetes and cardiac diseases [12].…”
Section: Follow-up Datamentioning
confidence: 59%
“…Other retrospective studies also reported that adjuvant chemotherapy (CDDP based combination regimens) alone showed favorable prognosis without severe complications ( 21 , 29 , 30 , 31 ). Although some previous studies showed that the survival benefits of adjuvant chemotherapy alone for high-risk patients with LNM and/or PI were similar to those of adjuvant RT, CCRT is considered the best treatment of node-positive cervical cancer, especially for adenocarcinomas, at present ( 32 ).…”
Section: The Retrospective Studies For Adjuvant Chemotherapy Without mentioning
confidence: 99%